Similarities and differences between western cultures: Toddler temperament and parent-child interactions in the United States (US) and Germany - Kirchhoff, C.; Desmarais, E.E.; Putnam, S.P.; Gartstein, M.A. (Infant behavior & development, 2019)
•Toddlers differed in perceptual sensitivity, soothability and attention shifting.•US and German dyads varied in domains of interactional engagement and stimulation.•Some relations between temperament and dyadic interaction differed between cultures. Parents play a critical role in shaping social-emotional development, particularly in early childhood; however, children’s influence on their own development is equally important. Parent-child interactions, fundamental to secure attachment and social schemes, represent a critical area of social-emotional development subject to child effects associated with temperament. The present study explores these effects through a cross-cultural lens via comparisons of dyads from the United States (US) and Germany. Specifically, cross-cultural differences in toddler temperament were evaluated via the Early Childhood Behavior Questionnaire (ECBQ; Putnam et al., 2006), with cross-cultural variability in parent-child interactions examined as well, along with differences in child temperament effects on the quality of these interactions. Ratings of temperament were generally similar between the two cultures; however, US toddlers were rated higher in attention shifting, whereas German children were rated higher on soothability and perceptual sensitivity. Additionally, dyadic interactions in the US were rated as more stimulating and demonstrating greater partner engagement than those in Germany. Differential contributions of temperament to interaction quality and complexity were also observed. Higher ratings of toddler discomfort and perceptual sensitivity predicted more stimulating interactions overall in the US but not Germany. In contrast, higher ratings of toddler low-intensity pleasure predicted more stimulating interactions in Germany but not the US. Overall, the present study identifies many similarities between US and German toddlers and supports theories describing children as active agents in shaping their own development, in what appears to be a different manner across cultures.